MICROWAVE ASSISTED SYNTHESIS AND CHARACTERIZATION OF SCHIFF BASE OF 2-AMINO BENZIMIDAZOLE (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
New Schiff base (2-[(1H-benzimidazol-2-ylimino) methyl]-4,6- diiodophenol) was synthesized by the condensation of aryl/hetero aromatic aldehyde (3,5diiodosalicylaldehyde) with 2- amino benzimidazole under conventional and microwave conditions and characterized through IR, HNMR and Mass spectral data and CHN analysis.